Analiza wrażliwości za pomocą funkcji IRR - Mielcarek, Jarosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
It is demonstrated that the IRR as a demand growth function which cannot be specified analytically is a reverse function of critical demand growth rate function. The second function is determined analytically and it enables to find the IRR function which presents how sensitive the IRR is to changes in demand. With the help of this function the sensitivity of the IRR margin safety rate as a percentage difference between cost of capital and an investment project IRR to changes in demand is assessed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 230-240